Pelatihan Matematika Bagi Tim Lomba Cepat Tepat (LCT) SMP Negeri 9 Kota Kendari Dalam Rangka Persiapan Mengikuti LCT Tingkat SMP/MTs se-Sulawesi Tenggara di FMIPA UHO - Somayasa, Wayan; Jufra, Jufra; Sani, Asrul; Djafar, Muhammad Kabil; Budiman, Herdi; Muhtar, Norma (Jurnal Pengabdian Masyarakat Singa Podium (JPMSIPO), 2023)
Title of this community service is “Mathematics Training for the Fast Precise Competition (LCT) Team at a SMP Negeri 9 Kendari in Preparation for Taking Part in LCT at SMP/MTs Level Throughout Southeast Sulawesi at FMIPA UHO”. Implemented with the aim of increasing the capacity of mathematics teachers at SMP Negeri 9 Kendari and improving the abilities of the LCT Team at SMP Negeri 9 Kendari in preparation for taking part in LCT level throughout Southeast Sulawesi at FMIPA UHO. The results of this community service activity are increased capacity of mathematics teachears and an increase in knowledge and abilities of the LCT Team at SMP Negeri 9 Kendari in the mathematics. The LCT Team SMP Negeri 9 is ready to take part in LCT Mathematics.